2017
DOI: 10.2147/ahmt.s109495
|View full text |Cite
|
Sign up to set email alerts
|

Update on the management of systemic juvenile idiopathic arthritis and role of IL-1 and IL-6 inhibition

Abstract: Systemic juvenile idiopathic arthritis (SJIA) is a disease marked with arthritis and several features of systemic inflammation including fevers, rashes, hepatosplenomegaly, lymphadenopathy, and serositis. The presentation can be variable and arthritis can be a later feature. Macrophage activation syndrome can be a life-threatening complication of this illness and requires early recognition and prompt therapy. Advancements in understanding the biology of SJIA have led to the development of cytokine-targeted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 78 publications
0
47
1
4
Order By: Relevance
“…Matrix metalloproteinase-8 (MMP-8), a collagencleaving enzyme released by neutrophils, is a key component in the degradation of extracellular matrix in conditions such as periodontitis, cardiovascular disease, rheumatoid arthritis, and cancer [1][2][3]. Interleukin-6 (IL-6), a proinflammatory cytokine secreted by macrophages and T cells in tissue damage and inflammation, is an important mediator in host response to infections and various autoimmune diseases [4][5][6]. During pregnancy, elevated levels of cervical and amniotic fluid (AF) MMP-8 and IL-6 have been linked to the process of cervical ripening and the impending onset of labor [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteinase-8 (MMP-8), a collagencleaving enzyme released by neutrophils, is a key component in the degradation of extracellular matrix in conditions such as periodontitis, cardiovascular disease, rheumatoid arthritis, and cancer [1][2][3]. Interleukin-6 (IL-6), a proinflammatory cytokine secreted by macrophages and T cells in tissue damage and inflammation, is an important mediator in host response to infections and various autoimmune diseases [4][5][6]. During pregnancy, elevated levels of cervical and amniotic fluid (AF) MMP-8 and IL-6 have been linked to the process of cervical ripening and the impending onset of labor [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Tocilizumab is a fully humanized monoclonal antibody against both soluble and membrane-bound IL-6 receptors. It is currently FDA approved for the treatment of SJIA and RA, and it has profoundly improved disease outcomes [166]. A study by Tappeiner et al has reported that two out of three patients with JIA-related uveitis responded to tocilizumab that was refractory to anti-TNF-α therapy [167].…”
Section: Tocilizumabmentioning
confidence: 99%
“…MAS may occur spontaneously, as a complication of active underlying disease, or may be triggered by an infection, a change in drug therapy, or toxic effect of a medication. The acute and dramatic onset of this entity often mimics a flare of the underlying disease or a severe sepsis [1]. Adenoviruses are emerging as an important cause of respiratory tract infections and can lead to significant morbidity in the immunocompromised.…”
Section: Introductionmentioning
confidence: 99%